KEKERABATAN BAHASA TETUN DAN BAHASA DAWAN (LINGUISTIK HISTORIS KOMPARATIF) - Detantri Bere; Kristofel Bere Nahak; Adeline Lelo Lein (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
This research aims to describe the relationship between the Tetun and Dawan languages which is entitled “The kinship relationship between the Tetun and Dawan languages” using the theory of comparative historical linguistics. The method used qualitative and quantitative approaches using a lexicostatistic technique. The data collection methodology and technique used are effective methods of observation, interviewing, and recording. This research was conducted at the village of Rafae, Raimanuk District, Belu Regency. The research instrument used in the interview was a list of questions containing 200 basics (Swadesh) vocabulary. The results showed that there was a relationship between the Tetun and Dawan languages, attempts through 33 pairs of related words, with 5 pairs of identical words category, phonetic match 10, phonetically similar 6, and a different phonemic 12. The level of kinship Bahasa Tetun and Bahasa Dawan has a kinship at the level of rock (stock) with a percentage of 16,5 %.